Effect of fertilization on yields and fodder value of winter pea cv. Maksimirski ozimi in triticale cv. Clercal mixture - Darko Uher; Zvonimir Štafa; Zlatko Svečnjak; Sulejman Redžepović; Mihaela Blažinkov; Dražen Kaučić (Mljekarstvo)
Two year field trials (1999 - 2001) were performed to determine theinoculation seed winter pea and nitrogen top-dressing effect on nodule dry weight of pea root and also on the dry matter yield of winter pea cv. Maksimirski ozimi and triticale cv. Clercal mixture. Immediately before sowing the inoculation of pea seeds was performed by the indigenous variety of Rhizobium leguminosarum bv. viciae which is part of Department of Microbiology collection at the Faculty of Agriculture University of Zagreb. The highest total nodule dry weight on pea root was determined on the inoculated variant 2 (0,635 g / variant). Total dry matter yields were ranging from 9,10 t ha-1 (control) up to 12,06 t ha-1 (nitrogen top-dressing). Crude proteins pea yields in 2001 were ranging from 798 kg ha-1 (nitrogen topdressing + inoculation) up to 1087 kg ha-1 (inoculation). For triticale, those values were from 568 kg ha-1 (control) up to 957 kg ha-1 (nitrogen topdressing). Total crude proteins mixture yield ranged from 1414 kg ha-1 (control) up to 1808 kg ha-1 (nitrogen top-dressing).